Dynamic capabilities developed by the interaction of individuals - Farkas, Tamás (Marketing & Menedzsment, 2023)
THE AIMS OF THE PAPER The existence of dynamic capabilities is key for newly created organizations. However, the development of these capabilities is less researched, especially in the case of start-ups. The primary aim of the study is to explore the characteristics of the development of dynamic capabilities through the case study of a domestic start-up, to illustrate the relationship between organizational and individual capabilities, while providing insights into the interaction between individual capabilities that can lead to the development of dynamic organizational capabilities. METHODOLOGY The primary data collection took place at a domestic start-up. The chosen methodology is the case study, in which three data sources were used. The in-depth interview served as the primary data source, personal or online interviews for at least 45 minutes were conducted with all members of the organization. The in-depth interviews were supplemented by document analysis to gather information from other sources. At the end of the study, the results were validated in a management workshop. MOST IMPORTANT RESULTS During the development of dynamic capabilities four types of interactions between individual capabilities could be identified: complementation, merging and extending similarities, searching and selecting alternatives and acceptance. Each type of interaction provides a solution in different situations, but all of them ultimately contribute to the development of dynamic capabilities. RECOMMENDATIONS Development of dynamic organizational capabilities (hence flexibility) is at least partly rooted in individuals and the interactions between them. It is therefore worthwhile for organizations to emphasize the acquisition of employees with good dynamic managerial capabilities and their involvement in interactions.